ASUHAN KEBIDANAN PADA NY “E’’ MASA HAMIL, BERSALIN, NIFAS, NEONATUS, DAN KELUARGA BERENCANA DI UPT PUSKESMAS BANGSAL MOJOKERTO - Dyah Siwi Hety, M.Kes; Leni Syarifatul Husna (MEDICA MAJAPAHIT, 2021)
The Maternal Mortality Rate in Indonesia is still high. The existence of comprehensive monitoring through Continuity of care (COC). Comprehensive services, which were complete services, starting from the period of pregnancy, parturition, post partum, neonatal and family planning, were carried out with midwifery management and SOAP documentation. Midwifery care was given to Mrs "E" G2P002. 38 weeks of gestational age was done at Puskesmas Bangsal working area on march 2020. The results of midwifery care performed on Mrs "E" pregnancy visit were obtained physiological complaint. After being given management according to the complaint then it could be overcame. When having parturition, Mrs. "E" was referred to Rs kartini and still had parturition through vaginal parturition, puerperal period of Mrs. "E" ran physiologically. Baby of Mrs "E" was born normal with a body weight of 3,300 grams and a body length of 50 cm, male sex. Neonatal period ran physiologically. The contraceptive method used by Mrs. "E" was 3 monthly contraceptive injection. Based on midwifery care at Mrs. "E" who experienced complaints of back pain was to encourge mother to maintain good posture,like when sitting choose to sit on a chair that has a back and the mother sits upright with the spine